[OP.1B.05] CEREBROPROTECTIVE EFFECT OF AN ANGIOTENSIN TYPE 2 RECEPTOR AGONIST DELIVERED VIA THE INTRANASAL ROUTE AFTER STROKE. (September 2017) - Sumners, C.; Bennion, D.; Jones, C.; Dang, A.; Isenberg, J.; Graham, J.; Waters, M.; Steckelings, U.
Abstract : Objective: The selective angiotensin type 2 receptor (AT2R) agonist Compound 21 (C21) has been proven in multiple preclinical studies to reduce infarct size and attenuate neurological deficits, when administered after ischemic stroke via intracerebroventricular or intraperitoneal routes. However, C21 has poor blood brain barrier (BBB) penetrability. Here, we used the novel and non-invasive intranasal approach to circumvent the BBB and deliver C21 directly to the brain via the upper olfactory region. The therapeutic efficacy of this intranasal trans-olfactory (INTO) application of C21 was assessed in a model of transient middle cerebral artery occlusion (MCAO). Design and method: (i) Ischemic stroke was elicited by endothelin-1-induced MCAO in 12-week old male SD rats. They were randomly divided into two treatment groups, receiving either 0.9% saline or C21 (1.5 ug/kg) delivered INTO at 1.5, 4, 24 and 48 h post-stroke, using a rat intranasal catheter device (Impel Neuropharma, Seattle, WA). All rats underwent blinded neurological assessments at 4, 24 and 72 h after MCAO, and immediately after the 72 h tests, were euthanized and cerebral infarct volumes were assessed by TTC staining. (ii) Male SD rats (12-week old) were implanted with a telemetry transducer (DSI, St. Paul, MN) into the abdominal aorta to measure blood pressure, heart rate and locomotor activity after INTO application of C21 (1.5 ug/kg) vs. 0.9% saline at baseline and post-ischemic stroke. Results: (i) Post-stroke INTO delivery of C21 (1.5 ug/kg) elicited a significant lowering of % cerebral infarct size (25.4 ± 4.7; n = 9) compared with saline-treated rats (48.4 ± 4.4; n = 21) [p < 0.05; two-way Mann-Whitney test]. The C21 (1.5 ug/kg)-treated rats also displayed highly significant improvements in neurological Garcia and Bederson scores (p < 0.01; two-way Mann-Whitney test]. (ii) INTO delivery of C21 (1.5 ug/kg) either in naïve rats (n = 7), or in rats post-stroke (n = 4), did not significantly alter baseline blood pressure, heart rate and locomotor activity. Conclusions: These results demonstrate, that INTO delivery of a low-dose of C21 in rats exerts protective effects after ischemic stroke, and suggest INTO administration as potential route of application of C21 to stroke patients.